HERMENEUTIKA OTORITATIF KHALED M. ABOU EL FADL: METODE KRITIK ATAS PENAFSIRAN OTORITARIANISME DALAM PEMIKIRAN ISLAM - Nasrullah Nasrullah (Hunafa: Jurnal Studia Islamika, 2008)
This paper deals with Abou El Fadl’s hermeneutical-authoritative concept. The hermeneutical athouritative emerges as an anti-thesis to all authoritative-interpretative concepts in Islamic thought. The authoritative- interpretative concept established on God’s name interpretation. This kind of interpretation claims that interpretation is an absolute right, without comropmizing with the interpretation of meaning with values of justice and contemporary issues of humanity, such as gender, jihâd issue and practice of democracy concept in Moslem countries.Kata Kunci:    hermeneutika otoritatif,  penafsiran otoritarianisme, pemikiran Islam, hukum Islam, jender